Atomic armor for thermal stability in nanoporous structures - Rui Yang; Qiaoling Si; Qiang Sheng; Mingyang Yang; Mu Du; Hu Zhang; Xiao-Lei Shi; Guihua Tang; Zhi-Gang Chen (Proceedings of the National Academy of Sciences, 2025)
Nanoporous structures play a critical role in a wide range of applications, including catalysis, thermoelectrics, energy storage, gas adsorption, and thermal insulation. However, their thermal instability remains a persistent challenge. Inspired by the extraordinary resilience of tardigrades, an “atomic armor” strategy is introduced to enhance the stability of nanoporous structures. Applied to mesoporous silica at parts-per-million levels, the atomic armor provides thermal resistance exceeding that of existing stabilization techniques. Thermal treatment at 1,000 °C for 168 h results in a fivefold increase in specific surface area, 66% lower thermal conductivity, and a sixfold increase in pore volume compared to untreated samples. Surface viscosity is linked to sintering resistance, and glass transition temperature and fragility are introduced as design parameters. Machine-learned interatomic potentials and metabasin escape algorithm-assisted molecular dynamics simulations are employed to reveal that materials traditionally classified as nonglass formers can exhibit glass transition temperatures and display intrinsic fragility. Alumina is identified as having a record-high glass transition temperature. By modulating the surface viscosity of nanoparticles, this approach stabilizes nanoporous structures effectively. The proposed method offers a simple and universal posttreatment process for improving the thermal stability of nanoporous structures.